PENGARUH KONEKSI POLITIK DAN CORPORATE GOVERNANCE TERHADAP AUDIT FEE - Primasari, Rahmaddian; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2013)
This study aims to examine and analyze the influence of political connections and good corporate governance of the audit fee. Political connections interpreted with government-owned companies and the owner of a company is a politicians. The implementation of good corporate governance using rank CGPI.This study is replication of research Wahab. Populations in this study is a company that follows survey exercised by IICG in the 2007-2011. This research using purpose sampling methods and the analysis used multiple regression.The result of study indicates that the company which has political connections can influence positive and significant to audit fee. Second, good corporate governance can influence positive and significant to audit fee.